SAT-114 Loss of DHEA-Targeting SULT2b1b Sulfotransferase Exacerbates Aggressive Traits of Prostate Cancer - Song, Chung Seog (J Endocr Soc, 2020)
The prostate-expressed sulfotransferase SULT2B1b (SULT2B) regulates intracrine androgen homeostasis by mediating 3β-sulfation of DHEA, thus reducing the precursor pool in the androgen biosynthesis pathway. We explored how loss of SULT2B might influence prostate cancer progression. Results show that SULT2B ablation in castration-resistant prostate cancer (CRPC) cells, generated by stable RNA interference or gene knockout, led to robust activation of the ERK1/2 Map kinase survival signal and induction of epithelial to mesenchymal transition (EMT). EMT activation was concluded on the basis of increased levels of vimentin (a mesenchymal protein) and the EMT-activating transcription factors SNAI1 (Snail) and TWIST1, shown by Western blotting, mass spectrometry and single-cell mass cytometry. Loss of SULT2B was associated with enhanced motility and invasive activity of CRPC cells in vitro and their growth escalation in vivo as xenografts. Higher invasion and metastasis potential of SULT2B-ablated CRPC cells was further indicated by results that these cells are less adhesive (i.e. easily detachable) and less stiff (i.e. more pliable) based on atomic force microscopy analysis of individual cells. Notably, AKR1C3, an aldo-keto reductase, which is elevated frequently in advanced prostate cancer, showed marked upregulation in SULT2B-deficient cells. AKR1C3 regulates androgen receptor (AR) signaling by promoting androgen biosynthesis and functioning as an AR-selective coactivator. While levels of AR and DHT did not change, AR activity was elevated, since PSA and FKBP5 mRNA induction by DHT-activated AR was several fold higher in SULT2B-silenced cells. The DHT-metabolizing AKR1C2 aldo-keto reductase was also upregulated, which likely accounts for a steady-state androgen level despite elevated AKR1C3 expression. Phosphorylation of ERK decreased in AKR1C3-silenced cells, signifying a causal link between AKR1C3 upregulation and ERK1/2 activation. SULT2B was undetectable immunohistochemically in tissue microarrays of clinical CRPC metastases, while SULT2B-negative samples showed AKR1C3-positive immunostaining. Primary prostate cancer exhibited variable, Gleason score independent SULT2B levels -- varying from strong positive to significantly reduced or undetectable. The reciprocal expression pattern for SULT2B and AKR1C3 in clinical CRPC suggests that AKR1C3 upregulation, ERK1/2 activation and increased aggressive traits of SULT2B-ablated cells, observed in vitro in cell models, may be clinically significant. Pathways regulating the inhibitory SULT2B-AKR1C3 axis may inform new avenue(s) for delaying disease progression in SULT2B-deficient prostate cancer.Funding Support: 1I01BX000280, VA (BC); W81XWH-14-1-0606, DOD (BC); IK6 BX004207, VA (BC); P50 CA97186, NIH & W81XWH-12-1-0208, DOD (EAM)